Ancient Turkic mythological texts in the “Kazakhstan Children’s Literature” university course - Nurgali К.Р.; Shashkina Г.З. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article is devoted to a comparative analysis of ancient Turkic myths with similar myths of the peoples of the world. Cosmogonic, anthropological, eschatological, etiological myths are considered in detail, as well as myths that have parallels among other peoples - the myth of a cultural hero, the Flood, the confusion of languages. O. Zhanaydarov’s book Myths of Ancient Kazakhstan is used as mythological texts. When considering the Turkic myths about the creation of the world and man, about the end of the world with similar myths of other peoples of the world, we can conclude that they are similar in typology and assume the presence of one source. The presence in the mythology of the pre-Kazakhs of a cultural hero (Nadulushe), similar to the image of Prometheus, confirms that ancient Turkic mythology had a fairly developed system of the pantheon of heroes. The myths about the global flood, about the confusion of languages, present in the Kazakh folk memory, except for some details, are identical with the biblical versions. The well-known myth about the origin of the Turkic tribe belongs to the archaic layer of ancient Turkic mythology and is typical for all Turkic-speaking peoples. The article affirms the idea that ancient Turkic mythology is a unique cultural heritage not only of our people, but of the entire world treasury, an equal heritage in the mythological family of the peoples of the world.